Effect of maltodextrin and gum arabic on antioxidant activity and phytochemical profiles of spray-dried powders of sapota (Manilkara zapota) fruit juice. Issue 3 (23rd October 2020) - Araujo, Hannah Caroline Santos; Jesus, M. S.; Leite Neta, M. T. S.; Gualberto, N. C.; Matos, C. M. S.; Rajan, M.; Rajkumar, G.; Nogueira, J. P.; Narain, N.
Abstract: This research work has an objective to analyze the phytochemical contents and antioxidant capacity in the spray-dried powders of sapota fruit using encapsulating agents of maltodextrin and gum Arabic. The phytochemical analysis and antioxidant activity of rehydrated dried powders of sapota using maltodextrin, gum Arabic and a mixture of these compounds were determined by FRAP, DPPH and ABTS assays. The retention of antioxidant activity and phenolic compounds in the rehydrated dried powders, when compared to fresh sapota juice, was due to the use of gum Arabic which was very efficient in protecting the sapota fruit and to avoid its oxidation.